Morley Safer's red China diary - Safer, Morley; Hewitt, Don (Hollywood : CBS News [production company] ; Kuala Lumpur : Visual Resources [distributor])
CBS News focused on the tour to 5 cities in China which are Yenan, Peking, Sian, Shanghai and Canton.
Executive producer, Don Hewitt ; editor, F. Howard O'neill, Richard W. Sears Jr
Keywords: China -- History; China -- Economic conditions